Fetal Biometric Parameters in USG for Early Detection of Fetal Growth Restriction - Himanshy Rai; Shambhavi Soni; Amaresh K. Shukla; Mohita Pandey; Mayank P. Singh; Vishnu K. Gupta (Journal of Pharmacy and Bioallied Sciences)
Background: Intrauterine growth restriction (IUGR) is a major pregnancy complication linked to adverse perinatal outcomes. Biometric parameters and Doppler velocimetry are valuable tools in diagnosing IUGR and predicting pregnancy outcomes. Objectives: This study aims to evaluate the role of biometric and Doppler parameters in the prediction of fetal growth restriction and associated pregnancy outcomes. Methods: The participants underwent ultrasound biometry, including abdominal circumference (AC), head circumference (HC), femur length (FL), and Doppler velocimetry of uterine and umbilical arteries. Pregnancy outcomes and associations between Doppler and biometric parameters with delivery outcomes were monitored. Results: Biometric findings showed that 52% of patients had abnormal FL/AC ratios, and 44% had abnormal HC/AC ratios. Doppler findings revealed that 85.7% of Left Uterine Artery Resistance Index (RI) and 82.1% of Right Uterine Artery RI measurements were normal. Additionally, 85.3% of Umbilical Artery RI values were normal. Significant associations were found between uterine artery RI and systolic/diastolic ratio (SD) and pregnancy outcomes (P < 0.05). Conclusion: Biometric parameters and Doppler velocimetry, particularly uterine and umbilical artery RIs and SDs, are essential in diagnosing IUGR and predicting pregnancy outcomes. These tools are valuable in identifying pregnancies at risk for complications, enabling timely management to improve maternal and fetal health.